The effects of viewing by scrolling on a small screen on the encoding of objects into visual long-term memory - Sho, Hayato; Morita, Hiromi (Frontiers in Psychology, 2023)
The perception of an image obtained by scrolling through a small screen can differ from the typical perception of a wide visual field in a stable environment. However, we do not fully understand image perception by scrolling on a small screen based on psychological knowledge of visual perception and cognition of images. This study investigated how screen size limitations and image shifts caused by scrolling affect image encoding in visual long-term memory. Participants explored the stimulus images under three conditions. Under the scrolling condition, they explored the image through a small screen. Under the moving-window condition, they explored the image by moving the screen over a masked image; this is similar to looking through a moving peephole. Under the no-window condition, participants were able to view the entire image simultaneously. Each stimulus comprised 12 objects. After 1 h, the samples were tested for object recognition. Consequently, the memory retention rate was higher in the scrolling and moving-window conditions than in the no-window condition, and no difference was observed between the scrolling and moving-window conditions. The time required by participants to explore the stimulus was shorter under the no-window condition. Thus, encoding efficiency (i.e., the rate of encoding information into memory in a unit of time) did not differ among the three conditions. An analysis of the scan trace of the scrolling and window movements in relation to the image revealed differences between the scrolling and moving-window conditions in terms of the scan’s dynamic features. Moreover, a negative correlation was observed between the memory retention rate and image-scrolling speed. We conclude that perceiving images by scrolling on a small screen enables better memory retention than that obtained through whole-image viewing if the viewing time is not limited. We suggest that viewing through a small screen is not necessarily disadvantageous for memory encoding efficiency depending on the presentation mode, and the results show that participants who scrolled fast tended to have worse memory retention. These findings can impact school education and thus suggest that the use of mobile devices in learning has some merit from the viewpoint of cognitive psychology.